2020
DOI: 10.3233/jad-200674
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions for Dementia Risk Reduction and Prevention Research: An International Research Network on Dementia Prevention Consensus

Abstract: In the past decade a large body of evidence has accumulated on risk factors for dementia, primarily from Europe and North America. Drawing on recent integrative reviews and a consensus workshop, the International Research Network on Dementia Prevention developed a consensus statement on priorities for future research. Significant gaps in geographical location, representativeness, diversity, duration, mechanisms, and research on combinations of risk factors were identified. Future research to inform dementia ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…We used a web-based dataset to enable a large-scale investigation of eight modifiable risk factors and cognitive performance over the adult lifespan. Past studies have been instrumental in demonstrating the prevalence and dose-response association of risk factors in older adults [12,15], which we build on to show that risk factor prevalence and the dose-response association varies over the adult lifespan. Our results extend previous findings to show that risk factors are more prevalent as age increases, and also show a larger dose-response association with cognition as age increases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used a web-based dataset to enable a large-scale investigation of eight modifiable risk factors and cognitive performance over the adult lifespan. Past studies have been instrumental in demonstrating the prevalence and dose-response association of risk factors in older adults [12,15], which we build on to show that risk factor prevalence and the dose-response association varies over the adult lifespan. Our results extend previous findings to show that risk factors are more prevalent as age increases, and also show a larger dose-response association with cognition as age increases.…”
Section: Discussionmentioning
confidence: 99%
“…We used cross-sectional data, which offers correlational associations between risk factors and cognitive outcomes. Past work has indicated that observational effects are not always replicated in experimental studies [12,42]. However, a meta-analysis confirmed a consistent causal effect of risk factors on longitudinal cognitive decline and incident dementia in people with no cognitive decline at baseline (n> 40,000 [15]).…”
Section: The Dose-response Association Of Risk Factors and Cognition Differs With Agementioning
confidence: 95%
See 2 more Smart Citations
“…The population attributable fraction of risk (which combines the relative risk with prevalence) for independent risk factors ranges from 1% (obesity, diabetes) to 8% (hearing loss) [ 7 ]. Behavioral and lifestyle factors can co-occur and the interplay between multiple risk factors is not yet well understood [ 9 , 10 ]. Models with Australian data that account for nonindependence suggest that reducing the rate of each risk factor by 20% could reduce the prevalence of dementia by up to 30% by 2050 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%